Cycles in language change - Bouzouita, Miriam; Breitbarth, Anne 1976-; Danckaert, Lieven 1984-; Witzenhausen, Elisabeth (Oxford studies in diachronic and historical linguistics, 2019)
"This volume explores the multiple aspects of cyclical syntactic change from a wide range of empirical perspectives. The notion of 'linguistic cycle' has long been recognized as being relevant to the description of many processes of language change. In grammaticalization, a given linguistic form loses its lexical meaning - and sometimes some of its phonological content - and then gradually weakens until it ultimately vanishes. This change becomes cyclical when the grammaticalized form is replaced by an innovative item, which can then develop along exactly the same pathway. But cyclical changes have also been observed in language change outside of grammaticalization proper." - Umschlag